2021
DOI: 10.3389/fgene.2021.604461
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of Peptidylprolyl Isomerase A Pseudogene 22/microRNA-197-3p/Peptidylprolyl Isomerase A Axis in Hepatocellular Carcinoma

Abstract: The burden of hepatocellular carcinoma (HCC) worldwide is increasing over time, while the underlying molecular mechanism of HCC development is still under exploration. Pseudogenes are classified as a special type of long non-coding RNAs (lncRNAs), and they played a vital role in regulating tumor-associated gene expression. Here, we report that a pseudogene peptidylprolyl isomerase A pseudogene 22 (PPIAP22) and its parental gene peptidylprolyl isomerase A (PPIA) were upregulated in HCC and were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…In breast cancer, the PPIA/CrkII axis modulates host antitumor immune escape [31]. In HCC, hypoxia increases immune infiltration through the PPIAP22/miR-197-3p/PPIA axis [32].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, the PPIA/CrkII axis modulates host antitumor immune escape [31]. In HCC, hypoxia increases immune infiltration through the PPIAP22/miR-197-3p/PPIA axis [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chen et al found that pseudogene PRELID1P6 was over-expressed in glioma and promoted glioma progression by affecting the cellular localization of hnRNPH1, thereby protecting hnRNPH1 from ubiquitin-mediated degradation which led to up-regulated TRF2 expression and activated the Akt/mTOR pathway ( Xi et al, 2021 ). In addition, highly expressed pseudogene PPIAP22 promotes hepatocellular carcinoma progression via up-regulating PPIA expression by acting as a ceRNA for miR-197-3p ( Gu et al, 2021 ). Moreover, our previous study revealed that pseudogene DUXAP10 is over-expressed in gastric cancer, and promoted cell proliferation and invasion via interacting with EZH2 and LSD1 to repress LATS1 transcription ( Xu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further study found that PPIAP22 may act as a ceRNA by sponging miR-197-3p to relieve repression of its parental gene peptidylprolyl isomerase A (PPIA). 184 Similar to PPIAP22, upregulation of PPIA is also associated with tumor size and poor patient survival and has been shown to promote tumor growth. 184 , 230 The expression levels of PPIAP22 or PPIA were correlated with the infiltration levels of tumor-infiltrating immune cells (TIICs), such as T cells, dendritic cells, and macrophages, and with the expression of several chemokines, including C-C motif chemokine ligand 15 (CCL15) and C-X-C motif chemokine ligand 12 (CXCL12).…”
Section: Regulation Of Ncrnas In the Crosstalk Between Macrophages An...mentioning
confidence: 99%
“… 184 Similar to PPIAP22, upregulation of PPIA is also associated with tumor size and poor patient survival and has been shown to promote tumor growth. 184 , 230 The expression levels of PPIAP22 or PPIA were correlated with the infiltration levels of tumor-infiltrating immune cells (TIICs), such as T cells, dendritic cells, and macrophages, and with the expression of several chemokines, including C-C motif chemokine ligand 15 (CCL15) and C-X-C motif chemokine ligand 12 (CXCL12). 184 Chemokines are likely also involved in the lncRNA HOTAIR-mediated relationship in HCC.…”
Section: Regulation Of Ncrnas In the Crosstalk Between Macrophages An...mentioning
confidence: 99%
See 1 more Smart Citation